TRANSIENT ANALYSIS OF BLOOD FLOW IN FUSIFORM MODELS OF AORTIC ANEURYSMS - VINOTH, R. (International Journal of Psychosocial Rehabilitation, 2020)
The Computational Fluid Dynamic (CFD) models of idealized fusiform aortic aneurysms and aortic arch with saccular aneurysm were developed to estimate hemodynamic parameters. The transient flow was simulated in aortic aneurysm models with laminar flow condition. The wall of aortic aneurysm was treated as rigid. The hemodynamic parameters flow velocity, wall pressure and wall shear stress (WSS) were estimated from fusiform aneurysm models. These observed hemodynamic parameters shows that, the aneurysms with larger diameter may cause disturbed flow. The variation in peak wall pressure value in all models is minimum. The wall shear stress has attained high value at peak systole in all models. The flow velocity was estimated from saccular aneurysm models. The flow velocity result shows a recirculation of flow in the saccular aneurysm region. The calculated hemodynamic parameters may help to understand the insights of flow in aortic aneurysm models.